2023
DOI: 10.1021/acscatal.3c01821
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Construction of Metal–Organic Frameworks as Smart Channels for the Effective Electrocatalytic Reduction of Nitrate at Ultralow Concentrations to Ammonia

Abstract: Electrochemical conversion of nitrate, a widespread water pollutant, into high-value-added ammonia is a renewable and delocalized route to restore the globally perturbed nitrogen cycle. However, premature desorption of catalytic intermediates and the competitive reaction of hydrogen evolution make the current performance still far from suitable for practical applications. In this work, a Zr-based metal−organic framework (MOF) is in situ constructed at the reaction interface to serve as a smart channel for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 77 publications
1
30
0
Order By: Relevance
“…At various applied potentials, the intensity of the bands in the spectra of Ni 1 Cu SAAO is significantly higher compared to that of Cu 2 O NWs, providing further evidence that the single-atomic Ni sites enhance water dissociation. Furthermore, as the applied potential decreases, the intensity of the downward bands at 1589, 1307, 1225, and 1145 cm –1 gradually increases, indicating the production of *NH 2 OH, *NO, NO 2 – , and *NH 2 intermediates, respectively. It is evident that the signal corresponding to NO 2 – on Cu 2 O NWs is stronger than that on Ni 1 Cu SAAO, particularly at lower overpotentials, suggesting a favorable NO 3 – -to-NO 2 – process on Cu 2 O NWs. Additionally, the band intensity assigned to the *NH 2 OH intermediates is more pronounced on Ni 1 Cu SAAO compared to that on Cu 2 O NWs at most of the applied potentials.…”
Section: Resultsmentioning
confidence: 94%
“…At various applied potentials, the intensity of the bands in the spectra of Ni 1 Cu SAAO is significantly higher compared to that of Cu 2 O NWs, providing further evidence that the single-atomic Ni sites enhance water dissociation. Furthermore, as the applied potential decreases, the intensity of the downward bands at 1589, 1307, 1225, and 1145 cm –1 gradually increases, indicating the production of *NH 2 OH, *NO, NO 2 – , and *NH 2 intermediates, respectively. It is evident that the signal corresponding to NO 2 – on Cu 2 O NWs is stronger than that on Ni 1 Cu SAAO, particularly at lower overpotentials, suggesting a favorable NO 3 – -to-NO 2 – process on Cu 2 O NWs. Additionally, the band intensity assigned to the *NH 2 OH intermediates is more pronounced on Ni 1 Cu SAAO compared to that on Cu 2 O NWs at most of the applied potentials.…”
Section: Resultsmentioning
confidence: 94%
“…[31] Another noticeable study was recently demonstrated by Yan, Yang, Wang, and coworkers, who utilized the similar concept in the electrochemical reduction of nitrate to produce ammonia (see Figure 4). [32] In this work, the CuÀ Zn electrocatalyst was located in the pores of the defective UiO-66, and it was found that the terminal carboxylic group present in the defective Zr-MOF could not only provide the secondary coordination interaction to stabilize the catalytic intermediate but also suppress the hydrogen evolution. The electrocatalyst, along with the defective UiO-66, could thus achieve high conversion, selectivity, and Faraday efficiency for converting low-concentration nitrate in the aqueous solution into ammonia.…”
Section: Zr-mofsmentioning
confidence: 89%
“…11a). 138 Both DFT and experimental results demonstrated a strong correlation, underscoring the pivotal role of the UiO-66 in enhancing selective eNO 3 RR by fine-tuning the adsorption energy of the *ONH route and curtailing the competing HER. The porous structure of the UiO skeleton modulated the proton transfer channels at the interface between the CuZn nanoclusters and the MOF, which is the primary factor contributing to the improved electrocatalytic performance of the eNO 3 RR.…”
Section: Metal–organic Interfacementioning
confidence: 96%